PERAN INFLUENCER PADA MEDIA SOSIAL INSTAGRAM DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN FRUTIVEZ - Nabilla Vynka Fakhira; Roni Kastaman; Totok Pujianto (Universitas Galuh, 2022)
The use of social media as a marketing tool provides a lot of convenience for consumers to get information about the products they need or want. Marketing through social media is also known as digital marketing. The purpose of this research is to determine whether there is a positive and significant influence between influencer marketing and brand image on buying decision. Descriptive quantitative methods were used in this research by distributing questionnaires for research data collection and randomization using purposive sampling technique to collect respondents who had bought products and followed Frutivez’s Instagram. Multiple regression analysis was used on the data obtained to determine the influence exerted by influencer marketing and brand image on consumer buying decisions. The results of this research show that influencer marketing, brand image, and the combination of the two variables have a positive and significant influence on consumer buying decisions with a strong influence based on the results of hypothesis testing in this study which shows that: (1) Influencer marketing has a positive and significant effect on buying decisions with a regression coefficient value of 0.581 ; (2) Brand image has a positive effect on buying decisions with a regression coefficient value of 0.298, and (3) Influencer marketing and brand image simultaneously have a positive effect on buying decisions, as evidenced with the coefficient of determination value of 0.705 indicating that the ability of the independent variables in explaining the variation of the dependent variable is 70.5%. This proves that the number of product sales from September to October is due to the influence of influencer marketing and brand image which has a positive and significant influence on consumer buying decisions to increase sales of Frutivez’s products.